2019
DOI: 10.5194/aab-62-99-2019
|View full text |Cite
|
Sign up to set email alerts
|

The influence of zinc-methionine bioplex supplementation to pregnant and lactating sheep on selected wool parameters

Abstract: The most important nutrients affecting wool production include sulfur amino acids, such as methionine, and minerals, such as zinc, and their deficiency may cause wool production decrease. The aim of this study was to evaluate an effect of zinc and methionine chelate addition on the qualitative characteristics of Merino ewes wool and zinc content in wool fibers and on their surface. Histological evaluation of fibers was also performed. The study included 22 Polish Merino ewes divided into two groups: control an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Furthermore, Zn supplementation to feed was also found to be effective on fibre diameter in the same study. The finding of the study showed that the sheep with additional Zn had higher than control groups [41].…”
Section: Fibre Diametermentioning
confidence: 78%
See 2 more Smart Citations
“…Furthermore, Zn supplementation to feed was also found to be effective on fibre diameter in the same study. The finding of the study showed that the sheep with additional Zn had higher than control groups [41].…”
Section: Fibre Diametermentioning
confidence: 78%
“…In brief, the effect of Fe on the fibre length was favourable, however, the effect of Mg and Zn were negative. The correlation between fleece Zn content and the fibre length was to be 0.60 in Merino sheep [41]. The correlation between fibre length-diameter and the fibre length-elasticity was found to be significant (p-value<0.05) and was 0.12 and 0.22, respectively.…”
Section: Fibre Lengthmentioning
confidence: 78%
See 1 more Smart Citation
“…Wool production and quality are also influenced by the sex and age of animals and ewe reproduction state (Khan et al, 2012 andScobie et al, 2015). Moreover, the role of proper nutrition reflected in energy-rich and protein supplement are of the main factors affecting the wool production (Nguyen, 2018 andWyrostek et al, 2019).…”
Section: Introductionmentioning
confidence: 99%